Digital Marketplace and Fintech Nexus - Dimas Bagus Wiranatakusuma; Anwar Allah Picthay; Fawwaz Ardhan Kencana; Satria Utama (CV. Era Digital Nusantara, 2026)
The rapid convergence of digital marketplaces and financial technology (fintech) is reshaping economic participation, particularly in emerging economies such as Indonesia. This study employs a Systematic Literature Review (SLR) of 20 Scopus-indexed articles to examine the integration of online marketplace platforms and fintech ecosystems. Guided by the PRISMA methodology and supported by VOSviewer bibliometric analysis, the review identifies dominant research themes including fintech adoption, blockchain-enabled commerce, digital financial services, information systems, and customer-centered innovation. Density visualization reveals fintech and commerce as the most intensively studied topics, while overlay visualization highlights blockchain, data marketplaces, and financial assets as emerging research trends during 2024–2025. Network visualization further classifies the literature into five thematic clusters covering artificial intelligence, commerce, information systems, competitive markets, blockchain, and global economies. The findings indicate that digital literacy, regulatory support, Sharia compliance, interoperability, and technological readiness are key determinants of successful marketplace–fintech integration. In addition, HALVORA (Halal Verification Retail Online Apps) is identified as an innovative digital platform that supports MSMEs by integrating halal verification, digital marketplaces, financial services, business networking, and entrepreneurship support within a single ecosystem. This integration enhances digital literacy, expands market access, improves business competitiveness, and accelerates digital transformation among entrepreneurs. Furthermore, HALVORA contributes to sustainable community economic empowerment by facilitating trusted halal commerce and strengthening the connection between digital marketplaces and fintech services. The review also identifies research gaps related to ethical governance, digital infrastructure, and integrated digital platforms, providing directions for future studies on inclusive, sustainable, and technology-driven marketplace–fintech ecosystems.